International Sign conference interpreters as a Community of Practice - de Wit, Maya; Crasborn, Onno; Napier, Jemina (Meta, 2024)
Conference signed language interpreters traditionally work between their national sign language and the national spoken or written language. During their careers, interpreters may add other spoken or signed languages to their repertoire. Some also acquire International Sign (IS) as a working language and interpret between IS and other signed and spoken languages. Being highly context dependent, IS has limited conventions and there is no established educational path toward learning to interpret IS. Generally, the acquisition of IS by any signer happens through interaction with signers of other signed languages. In this article, we explore the concept of IS conference interpreters as a Community of Practice (CoP), where novices acquire and experienced IS interpreters further their IS interpreting competences through situated learning. Such learning in practice may ultimately lead to the development of interpreting expertise and expert performance in IS conference interpreting. We present new data from a 2019 global survey of IS conference interpreters and follow-up interviews with eleven selected survey respondents. The results of our study suggest that there is indeed a CoP of IS conference interpreters and that it is essential for individual interpreters to participate in that community to develop the required competences and professional practices.